β-Lactone Derivatives and Their Anticancer Activities: A Short Review - Wang, Jun; Shi, Yumin; Jiang, Dan (Current Topics in Medicinal Chemistry, 2021)
Cancers, a set of genetic diseases that can change the behavior and cell growth in body tissues, are the second leading cause of death across the world. Several treatment approaches, such as radiation, immunotherapy, and chemotherapy, can be applied to cure cancer, and among them, chemotherapy is one of the primary treatments for cancer, in which chemotherapeutic drugs are used. Great achievements have been made in the development of novel anticancer agents, but drug resistance is usually generated quickly, making overcoming drug resistance or developing more effective anticancer agents an imperative challenge. β-Lactones (2-oxetanones) are chemically diverse and often referred to as privileged structures for the discovery of new drugs, including anticancer agents. Marizomib (Salinosporamide A), a naturally occurring β-lactone proteasome inhibitor derived from the marine actinobacterium Salinispora tropica, has been termed as an orphan drug against multiple myeloma. Therefore, β-lactones are useful scaffolds for the discovery of novel anticancer agents. This review is an endeavour to highlight the advances in β-lactone derivatives with anticancer potential. The synthetic strategies, structure-activity relationships, as well as modes of action, are also discussed to pave the way for further rational design.
Keywords: Structure-activity relationships